2004
DOI: 10.2307/1593666
|View full text |Cite
|
Sign up to set email alerts
|

Principals' and Teachers' Perceptions of Learning Disabilities: A Study from NARA Prefecture, Japan

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Sage Publications, Inc. and Hammill Institute on Disabilities are collaborating with JSTOR to digitize, preserve and extend access to Learning Disability Quarterly.Abstract. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Furthermore, the majority of teachers considered that the educational support received by teachers is not adequate; many teachers viewed that dyslexia is neglected in the Algerian education system where there is no help provided to accommodate students needs. Hence, as claimed in the literature these issues hamper teachers from teaching those with dyslexia according to their needs (Kataoka et al, 2004).…”
Section: -Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the majority of teachers considered that the educational support received by teachers is not adequate; many teachers viewed that dyslexia is neglected in the Algerian education system where there is no help provided to accommodate students needs. Hence, as claimed in the literature these issues hamper teachers from teaching those with dyslexia according to their needs (Kataoka et al, 2004).…”
Section: -Discussionmentioning
confidence: 99%
“…According to Elias (2014), teacher knowledge and awareness of dyslexia are of paramount significance in understanding the learners' needs, having positive attitudes toward affected learners and helping them overcoming their difficulties as well as improving their attainment levels. Contrary to that, a research investigation carried out by the Ministry of Education in Japan showed that teachers were not even aware if their learners are struggling with particular learning difficulties or not (Kataoka et al, 2004). In the same manner, Sónia, (2012) in her research conducted in Portugal found that teachers are not aware of dyslexia where they also felt powerless to provide help because they see that they are not pedagogically equipped to meet the need of their learners with dyslexia.…”
Section: -2 Dyslexia and Teachers' Unawareness And Misunderstandingmentioning
confidence: 94%
“…Ineffective classroom teaching was termed as a signi cant contributor in causing learning disabilities. Teachers reported that students with learning disabilities were not receiving appropriate support from the school (Kataoka et al, 2004). Their study noted the following implications,…”
Section: Teachers' Perceptions In Other Countriesmentioning
confidence: 99%
“…Attitudes are usually a result of one's perceptions of the situation and therefore it is important to understand both to get an overall picture of the factors that can influence teachers' work with students with disabilities. Some of the studies that seem to be directly concerned with teachers' perceptions suggest, for example, that teachers may display a hierarchy of preference in whom they favour to work with, which might relate to the type of impairment an individual has (Kataoka et al, 2004). Others point out that such perceptions may also impact on some external characteristics, such as hyperactivity, being spotted more often in those with a particular condition, such as learning disability (Smith-Bonahue et al, 2009).…”
Section: Introductionmentioning
confidence: 99%